The Effect Of Gym Brain Approach To Increasing Cognitive Functions In Elderly In Panti Werdha Melania Jakarta - Ira Mayasopa; Royani (STIKes IMC Bintaro, 2019)
Elderly is the final stage of the human life cycle that will be experienced by every individual naturally. Being elderly means that someone has gone through 3 stages of life, namely children, adults to old age. In this phase the elderly experience many changes both physically and mentally, especially setbacks in various bodily functions and abilities that they have had. One of them is cognitive decline. One effort to prevent decline or improve cognitive function is by Brain Gym. The purpose of this study was to determine the effect of Brain Gym Giving on Increasing Cognitive Function in the Elderly at Melania Nursing Home Jakarta. This type of research is quantitative with research on Quasi Experimental Design One Pretest-Post Test Group. The study population was all the elderly who lived in the orphanage totaling 35 elderly. The sampling technique uses purposive sampling. Data analysis method uses Paired Sample T Test. The results of analysis before and after the Paired Sample T Test show p knowledge value of 0,000 with a standard p value <0.05. Conclusion: there is an effect of giving brain gym with an increase in cognitive function in the elderly.